The Effect of Internal Control, Information Technology and Audit on Good Amil Governance Practices - Fera Yolanda; Muhammad Hasbi Zaenal; Sigid Eko Pramono (Center of Strategic Studies (PUSKAS) BAZNAS, 2020)
This research aimed to find out how strong the effect of the implementation of internal control, information technology and audit on Good Amil Governance. In this research, the respondents were the chief and amil at BAZNAS in South Kalimantan. The type of this research was exploratory with data collection technique using questionnaire. Data analysis method that was used in this research was descriptive analysis method, Structural Equation Modeling (SEM) with software of SmartPLS 3.0. The research result showed that the variables of internal control, information technology, and audit had significant and positive effect on good amil governance.